Alternative Questions in English: (Functional-Pragmatic Analysis) - Mkhitaryan, Yelena; Sargissyan, Sona (Armenian Folia Anglistika, 2010)
Alternative questions in English, as well as other interrogative sentences, can fulfil functions of direct and indirect speech acts expressing various pragmatic meanings (advice, threat, resentment, etc.). From the point of view of the form and structure, such interrogative sentences can be different in nature. In certain cases interrogative sentences with the conjunction or do not possess an alternative meaning.